Initial growth and biomass of the species used as green fertilization in the alley cropping - Freitas, Bruna Bandeira de; Pauletto, Daniela; Sousa, Iara Rayana Leal de (Revista Verde de Agroecologia e Desenvolvimento Sustentável, 2020)
The objective of this work was to evaluate the initial growth of perennial species as gliciridia (Gliricidia sepium) and inga-xixica (Inga heteraphylla) and the performance of the biomass production of herbaceous species such as crotalaria juncea (Crotalaria juncea L.) and jack beans (Canavalia ensiformis DC.), used for green manure. Monitoring of species growth was followed for six months. To evaluate the biomass, the plants were pruned close to the soil, where the total plant material was obtained to determine the green mass weight, and four samples were taken from each plot to obtain the dry mass. The final height growth for inga-xixica was 0.77 m and 1.81 m for gliricidia. Absolute growth rates (TCA) for total height (Ht) differ between both species, in which the average of gliricidia has the highest value, 5.06 cm mes-1 in Ht, and that of inga-xixica is 2.68 cm mes-1. In the total biomass evaluation there was a difference between the two species, both for green and dry mass, with the best jack beans biomass in the two evaluations with the highest fresh biomass productivity of 8.6 t ha-1 and dry 1.6 t ha-1. For use in green manure, the perennial species gliricidia, which presented the best dendrometric parameters, and the herbaceous species jack beans, with the highest biomass production.